Tarkan Hatun (ok. 1055-1094). Cersei Lannister seldżuckiego dworu - Gajec, Marcin (Studia Azjatystyczne, 2017)
Tarkan Khatun was definitely one of the most powerful figures at the Seljuk court by the end of the 11th century. Born in an eminent Karakhanid house, the Turkish princess got down in the history as a talented politician and a skillful manipulator. She gained major power, surrounded herself with talented and ambitious advisors and, furthermore, she challenged the mighty vizier Nizam Al-Mulk. Tarkan’s involvement in organizing the assassination of an old advisor of her husband sultan Malikshah still remains quite mysterious and questionable, however some sources connect her to this affair. Tarkan lost three of her four children. Her two sons, Dawud and Ahmad, died at a young age. Her daughter, Mahmalak, has wed the Abbasid Caliph Al Muqtadi but this unhappy marriage culminated in a premature death of the young princess. No wonder that later on Tarkan gave all of her attention and energy to ensure safety and succession of her youngest son, Mahmud,. Consequently, in 1092, after the mysterious death of her husband, she took part in “a game of thrones” of Great Seljuks which, as a result, plunged the whole Near East into chaos for the next three years. Her struggles, which were not always successful, caused Tarkan’s grief. Ambitious Karakhanid succumbed to illness - the same one that later took away her last son. However, Tarkan was ahead of her times. The status that she has gained in the misogynistic society of the Muslim East definitely deserves our respect and appreciation.